Factors Affecting Patulin Production by Penicillium expansum in Apples - Tamara Edina Gal; Ersilia Călina Alexa; Renata Maria Șumălan; Ionuț Dascălu; Olimpia Alina Iordănescu (Foods)
The main mycotoxin found in apples is patulin (PAT), mostly produced by Penicillium expansum, during the storage of fruits. It is very difficult to control the quality of every fruit that enters the processing line, so there is a high probability that apple juice, applesauce, apple cider, even products intended for babies, contain moldy fruits, with PAT content. This review paper provides detailed information about the extrinsic and intrinsic factors that affect PAT prevalence in apples. Extrinsic factors, such as temperature, air composition in the storage room or packaging material, play a key role in infection with P. expansum and PAT accumulation. Lower temperatures often prevent fungal growth and the production of the mycotoxin, whereas higher or unstable temperatures can promote the buildup of the toxin in infected fruits. Controlled atmosphere storage appears to inhibit the accumulation of PAT in apples. In terms of internal composition, variations in the pH of the fruits and flesh firmness significantly impact fungal growth and PAT production in the fruits. The presence of ethylene, sucrose and polyphenols are some of the decisive chemical components that regulate PAT buildup. Susceptibility of different cultivars is also genetically driven, but the size of the decay area and the toxin-producing capacity of the fungal strain have noteworthy influence as well. Knowledge of these elements helps to understand the mechanisms of PAT production.